An ADRC-based backstepping control design for a class of fractional-order systems. (February 2022) - Doostdar, Fatemeh; Mojallali, Hamed
Abstract: A combined fractional tracking controller based on backstepping and active disturbance rejection control (ADRC) is proposed in this work to control uncertain fractional-order systems (FOSs). The proposed method is constructed in two parts: first, all internal and external uncertainties are estimated by a fractional-order extended state observer (FO-ESO). Second, fractional backstepping method is used to determine the control law and lead the system to the desired control objectives. The control system stability is verified by fractional Lyapunov-like lemma and two numerical simulations confirm the efficiency of the proposed combined ADRC-based backstepping controller. Highlights: A combined fractional controller is proposed based on backstepping and active disturbance rejection control. The proposed controller is presented for tracking problem of uncertain fractional-order systems. The estimation of system uncertainties is provided using an extended state observer. The superior performance of the proposed control method is confirmed by simulation results.